Malaria parasitemia and its association with CD4 cells, viral load and haematological parameters among HIV-infected children < 15 years in the Bonasssama Health District, Douala, Cameroon: Prevalence and risk factors - Ambe Fabrice Ngwa; Ekwi Damian Nsongmayi; Tanyi Pride Bobga; Bih Vanessa Tita; Judith Ngong Nyeme; Nyanjoh Eugine Mbuh (Parasite Epidemiology and Control)
Background: One of the major causes of morbidity and death in children is malaria, and HIV infection and other factors may make the situation worse. This study aimed to assess the prevalence of malaria parasitemia among HIV-infected children under 15 years in the Bonassama Health District, Douala, Cameroon, and investigate its association with CD4 cell counts, viral load, and haematological parameters. Methods: The study was a cross-sectional study involving 287 HIV-infected children <15 years and convenient sampling was used to enrol participants. A semi-structured questionnaire was used to obtain the characteristics of the participants from the caregivers. Venous blood was collected; blood films were made and stained using Giemsa for parasite detection. Full blood count, CD4 level and viral load were measured using a haematology auto-analyzer, pima counter and genexpert, respectively. Data were analysed using SPSS, and the chi-square test was used to assess the association. Predisposing factors to malaria were evaluated using multivariable logistic regression, and a p < 0.05 was considered significant. Results: The overall prevalence of malaria and anaemia was 31.01 % and 25.44 %, respectively. Malaria prevalence was significantly higher in children <5 years (42.68 %, p < 0.001), those presented with fever (40.70 %, p = 0.047), children not on antiretroviral therapy (ART) (28.6 %, p = 0.02) and cotrimoxazole (28.6 %, p = 0.02). Children <5 years (AOR = 1.81, 95 % 1.19–2.75), those between 5 and 9 years (AOR = 1.61, 95 % CI 1.11–2.48), children not on ART(AOR = 2.2, 95 % 1.03–4.74) and Cotrimoxazole (AOR = 9.08, 95 % 2.33–43.46), febrile children (AOR = 1.72, 95 % 1.01–2.11), children with viral load >3000 copies/μL(AOR = 2.933, 95 % 1.36–6.49), and CD4 count <200cells/ μL (AOR = 3.09, 95 % 2.08–4.6) were factors associated with malaria parasitemia among HIV-infected children. Haemoglobin levels (p = 0.0016), White Blood Cells (p = 0.002), Red Blood Cells (P < 0.001), neutrophils count (p < 0.001), and platelet counts (p = 0.0164) were significantly lowered among malaria/HIV children compared to HIV-infected children. Conclusion: The study concludes that HIV-infected children under 5 years, especially those not on ART or cotrimoxazole, are at a significantly higher risk for malaria and related haematological issues. This underscores the necessity for targeted malaria screening and treatment in this vulnerable group. Public health strategies should prioritize enhancing access to ART and cotrimoxazole to mitigate these risks and improve overall health outcomes.